Water mass reconstruction by Nd isotopic analysis from Mid Atlantic oceanic sediments - Ferreira, maria Luiza de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Nd isotopic information obtained of Fe-Mn oxyhydroxide coatings marine sediment is used to reconstruct the interplay of water masses in the Mid Atlantic Ocean during the past 22 ka. The method consist of leaching those coatings and measure in Mass Spectrometer to define the εNd values (ε notion that compare the ratio 143Nd/144Nd in terms of their deviation from the Chondritic Uniform Resevoir (CHUR) evolution line) correspondent to past bottom sea water. The radiogenic or unradiogenic parameter of waters with Southern and Northern source (SSW and NSW) was captured for the sediments coating and is used to identify their influence in the surrounded area of the studied core at 22 000 years until present. The core is localized in Mid Atlantic Ocean and was collected in the IODP program in site 306 core U1313. The results had presented convinced records, giving evidence that during Holocene deep waters did not experience distinguished changes; the influence of NSW indicating a reduce but not the shutdown of deep water formation in North Atlantic during LGM; and the record data suggest possible contributions of eastern water mass into Mid Atlantic during glacial time

Informações isotópicas de Nd obtidas da capa oxidada ferromanganífera de sedimentos marinhos são usadas para reconstruir a interação de massas de água no Oceano Atlântico Médio durante os últimos 22 ka. O método consiste na proxy εNd aplicada nos sedimentos, que consistem em dissolução destes revestimentos com o intuito de isolar o isótopo de Nd, posteriormente medições em espectrômetro de massa são feitas para definir os valores εNd (ε notação que compara ao razão dos isótopos 143Nd/144Nd em termos do seu desvio a partir da linha de evolução do “Chondritic Uniform Resevoir” (CHUR)) correspondentes a porção inferior das águas marinhas do passado. O caráter radioativo ou não radioativo de Águas Originárias do Sul e do Norte (SSW e NSW) foi capturado nestes revestimentos dos sedimentos que são utilizados para identificar a influência destas águas na área em que o testemunho estudado durante 22 000 anos até o presente. O testemunho (IODP site 306 core U1313) está localizado no Oceano Atlântico (porção central) e foi coletado no programa IODP. Os resultados apresentaram registros convincentes, dando evidências de que durante o Holoceno as águas profundas do oceano Atlântico não experimentaram fortes mudanças, também de que a influência de NSW indica uma redução e não uma parada no processo de formação de águas profundas no Atlântico Norte, os dados ainda podem sugerir possíveis contribuições de massas de água provindas da porção leste do oceano na porção central deste durante o período glacial
Keywords: Geologia estratigráfica; Espectrometria de massa; Sedimentos marinhos; Neodímio - Isótopos; Atlantico, Oceano